PENGARUH COMPUTER ANXIETY DENGAN COMPUTER ATTITUDE SEBAGAI MODERATING TERHADAP COMPUTER SELF EFFICACY GURU SEKOLAH DASAR NEGERI DI KELURAHAN PAHLAWAN PALEMBANG - Lindawati Lindawati (Jurnal Digit, 2018)
Abstrak This study aims to analyze the influence of computer anxiety to computer self efficacy and the influence of computer attitude as moderating relationship between computer anxiety to computer self efficacy of elementary school teacher in utilization of information technology. The object of this research is all teachers who teach in public elementary school in Palembang Heroes Village. In the research model, used 2 (two) method of data analysis, that is Regression Analysis for hypothesis 1 and Moderated Regression analysis (MRA) for hypothesis 2. Hypothesis 1 stated that computer anxiety have positive effect to computer self fficacy and hypothesis 2 states that computer atitude as moderating negatively affect the relationship between computer anxiety to computer self efficacy of public elementary school teacher in Palembang Pahlawan Village. Keywords: computer anxiety, computer attitude, computer self efficacy.